Penerapan Diversi dalam Penetapan Nomor 5/Pen.Div/2023/PN Kot Jo Nomor 18/Pid.Sus-Anak/2023/PN Kot - Ulin Najikhah; Arina Novitasari; Dika Anggara Putra; Dian Rosita (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The application of diversion in the juvenile criminal justice system aims to prevent children from undergoing formal legal proceedings that could negatively impact their development. This study analyzes the implementation of diversion in Decision Number 5/Pen.Div/2023/PN Kot Jo and Number 18/Pid.Sus-Anak/2023/PN Kot, involving a 15-year-old minor as the perpetrator of a minor offense. The study highlights the judge's considerations in determining diversion, including the child's age, the type of offense, and the offender's social background. Furthermore, this research examines how the principles of restorative justice are applied through diversion deliberations involving the offender, the victim, their families, and other relevant parties. The findings indicate that diversion in this case successfully reached a voluntary agreement, requiring the offender to return the item and compensate the victim. This agreement not only aims to prevent the negative impact of formal judicial proceedings but also provides an opportunity for the child to rehabilitate and reintegrate into society. These findings emphasize that when implemented effectively, diversion mechanisms can serve as an efficient solution for resolving juvenile delinquency cases without resorting to litigation.